Development of Local Wisdom-Based Teaching Materials for Learning to Write Fantasy Stories to Foster Character Education - Sari Ani; Laila Tri Lestari; Anisa Ulfah; Melisa Agustina; Melinda Agustin (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
Teaching materials play an essential role in facilitating effective learning and achieving instructional objectives. This study aimed to develop local wisdom-based teaching materials for learning to write fantasy stories and to examine their validity, practicality, and effectiveness in fostering character-oriented literary learning. The study employed a Research and Development (R&D) approach using the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The needs analysis and preliminary study were conducted at SMP Muhammadiyah 8 Laren and served as the basis for designing the teaching materials. During the development stage, the product was validated by experts in literary learning and teaching materials development. The validation results yielded scores of 93.6% and 96%, indicating that the teaching materials were highly valid and suitable for classroom implementation. The product was subsequently tested with 18 seventh-grade students. The findings revealed that the average positive responses from teachers and students reached 95% and 97.6%, respectively, demonstrating a high level of practicality. Furthermore, the post-test results showed an improvement in students' learning outcomes, indicating the effectiveness of the developed materials. Overall, the findings suggest that the local wisdom-based teaching materials are valid, practical, and effective for use in learning to write fantasy stories while supporting character education. These materials are recommended for teachers seeking to integrate local wisdom into literary learning, and future studies are encouraged to involve larger samples and employ experimental or classroom action research designs